Fine structure of NQR spectra in GaSe - Kovalyuk, Z.D.; Lastivka, G.I.; Khandozhko, О.G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
Peculiarities of the observation of nuclear quadrupole resonance (NQR) in
GaSe crystals grown from melt are under investigations. The splitting of a resonance
NQR line by two identical spectra is caused by the availability of non-equivalent
positions of Ga atoms in the polytypes e, y and, probably, o. The appearance of a fine
structure in NQR spectra is related to ordering in the system of the lattice defects
(polytypes), when the atomic Se-Ga-Ga-Se layers are stacked during the crystal growth.